The extent of periodontal disease and the IL-6 174 genotype as determinants of serum IL-6 level - Taina Raunio (Blackwell Synergy, 2007)
Aim: To study the extent of periodontal disease and the IL-6 174 genotype as determinants of serum and mouthwash IL-6 concentration in subjects with moderate to severe periodontal disease. Material and Methods: Fifty-two generally healthy subjects volunteered to participate. Probing pocket depth (PD) and periodontal attachment level (AL) were clinically examined and alveolar bone level (BL) was measured on orthopantomographs. IL-6 concentrations in mouthwash, collected by rinsing with 3ml saline for 30 s and in serum, obtained by venipuncture, were measured using ELISA. IL-6 174 polymorphism was studied using a polymerase chain reaction. Results: Eleven subjects carried the GG genotype, and 41 subjects, carried the CG/CC genotype. The mean ( SD) concentration of IL-6 in serum was 1.6 ( 1.5) pg/ml and, 2.8 ( 5.04) pg/ml in mouthwash. The serum concentration of IL-6 was higher in subjects with the GG genotype than with the CG/CC genotype. In regression analyses the percentages of sites with PDX6 mm, ALX6mm and BLX8 mm, the IL-6 174 genotype, body mass index and gender associated significantly with serum IL-6 concentration. Conclusions: The extent of moderate to severe periodontal disease and the IL-6 174 genotype contribute significantly to serum IL-6 concentration.